2017
DOI: 10.1177/1460458217720398
|View full text |Cite
|
Sign up to set email alerts
|

Predictors in starting and stopping Internet use between 2002 and 2012 by Dutch adults 65 years and older

Abstract: Research has indicated the need to consider the ageing process with technology adoption by older adults. This study examined psychological, health, social and demographic predictors with starting and stopping Internet use by older adults (2002-2012). Data were used from the Longitudinal Aging Study Amsterdam, and Cox regression analyses were done to test predictors over time with starting or stopping Internet use. The results indicated that older adults starting to use the Internet (11.6%) outnumbered those wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…In particular, specific internet activities could be addressed. Also, more specific cognitive outcomes could be examined, such as information processing speed, cognitive flexibility, and magnetic resonance imaging (Slegers et al, 2009;Webster et al, 2017), and more pertinent confounders could be added, such as vision impairment and personality (Gell et al, 2015;Berner et al, 2017). If replicated, our findings may warrant well-designed intervention studies (Klimova, 2016;Yates et al, 2016).…”
Section: Conclusion and Recommendationmentioning
confidence: 84%
See 1 more Smart Citation
“…In particular, specific internet activities could be addressed. Also, more specific cognitive outcomes could be examined, such as information processing speed, cognitive flexibility, and magnetic resonance imaging (Slegers et al, 2009;Webster et al, 2017), and more pertinent confounders could be added, such as vision impairment and personality (Gell et al, 2015;Berner et al, 2017). If replicated, our findings may warrant well-designed intervention studies (Klimova, 2016;Yates et al, 2016).…”
Section: Conclusion and Recommendationmentioning
confidence: 84%
“…Research has indicated that it is possible to compensate for changes in the aging brain, as seen with some older adults (Cabeza et al, 2002). Using the internet may help older people to train certain tasks, which in turn may help them to avoid losses and foster maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Covariates were selected a priori on the basis of previous studies showing associations between these variables and the exposure and outcomes of interest. Covariates assessed in this study were age and sex, as they are both independently associated with differences in internet use (Hogeboom et al, 2010;Choi and Dinitto, 2013;Berner et al, 2017;Bol et al, 2018;Office for National Statistics, 2018a;Quintana et al, 2018), loneliness and social isolation (Kobayashi and Steptoe, 2018). Sex was reported as male or female.…”
Section: Covariatesmentioning
confidence: 99%
“…Age was input in categories of 50-59, 60-69, 70-79, 80-89 and 90+ years. Marital status (married/living as married versus single) has also been associated with internet use (Hogeboom et al, 2010;Berner et al, 2017), social isolation and loneliness (Peplau, 1985;Grenade and Boldy, 2008;Steptoe et al, 2013b;Hawkley and Kocherginsky, 2017;Kobayashi and Steptoe, 2018). Socio-economic status (SES) was assessed using household non-pension wealth as this has been identified as an appropriate indicator of SES in older adults (Banks et al, 2004) and used in previous studies utilising the ELSA data-set Smith et al, 2015;Quintana et al, 2018;Jackson et al, 2019aJackson et al, , 2019b.…”
Section: Covariatesmentioning
confidence: 99%
“…As a third layer of concentric circles in our HIDECO theoretical framework presented in Figure 1, we highlight the relevance of technological and scientific progress and the historical changes therein for adult development and aging. In particular, technological advances over the last century have tremendously shaped more or less each and every aspect of daily life, including communication opportunities, managing money, access to health care services, and assisting with everyday tasks such as shopping or travel (Berner, Aartsen, & Deeg, 2019; Wright, 2012). As a consequence, technology promises to help and facilitate how people adjust to and compensate for age-related declines (Chen & Chan, 2011; Lindenberger, Lövdén, Schellenbach, Li, & Krüger, 2008).…”
Section: Historical Change and Adult Development: Mechanisms And Path...mentioning
confidence: 99%